Further Exploration of the Benzimidazole Scaffold as TRPC5 Inhibitors: Identification of 1‐Alkyl‐2‐(pyrrolidin‐1‐yl)‐1H‐benzo[d]imidazoles as Potent and Selective Inhibitors. (24th May 2022) - Sharma, Swagat; L. Pablo, Juan; Tolentino, Kirsten T.; Gallegos, Wacey; Hinman, Jennifer; Beninato, Madison; Asche, MacKenzie; Greka, Anna; Hopkins, Corey R.
Abstract: The transient receptor potential cation channel 5 (TRPC5) plays an important role in numerous cellular processes. Due to this, it has gained considerable attention over the past few years as a potential therapeutic target. Recently, TRPC5 has been shown to be involved in the regulation of podocyte survival, indicating a potential treatment option for chronic kidney disease. In addition, a recent study has shown TRPC5 to be expressed in human sensory neurons and suggests that TRPC5 inhibition could be an effective treatment for spontaneous and tactile pain. To understand these processes more fully, potent and selective tool compounds are needed. Herein we report further exploration of the 2‐aminobenzimidazole scaffold as a potent TRPC5 inhibitor, culminating in the discovery of 16 f as a potent and selective TRPC5 inhibitor. Abstract : Inhibitors with potential ! Medicinal chemistry optimization of the original hit compound, AC1903, 1, led to the formation of a next‐generation transient receptor potential cation channel 5 (TRPC5) inhibitor, 16 f . We profiled this compound in in vitro and in vivo pharmacokinetic assays as well as additional selectivity assays.